Injury risk (burden), risk matrices and risk contours in team sports: A review of principles, practices and problems - Fuller, C. W. (Sports Medicine, 2018)
The aim of this review was to provide insights into and a critical assessment of injury burden, risk matrices and risk contours in the context of team sports. Injury burden is the product of injury incidence and mean severity, and is normally reported as days` absence/1000 player-hours. An important feature of injury burden is that equal values can reflect quite different numerical combinations of injury incidence and severity. The timeframe over which injury burden affects a team depends on the incidence and severity values of the injuries sustained. Injury burden is evaluated through the use of risk matrices and risk contours. The main benefits of using risk matrices, and the reasons for their widespread acceptance, are the minimal data inputs required, the ease of understanding the visual data presentation, the transparent nature of the evaluation criteria and the simplicity with which the conclusions can be communicated to stakeholders. Injury burden is most often used for the identification of injuries that cause the greatest loss of time for players, ranking the importance of injury risk factors and prioritising injury prevention plans. Although risk matrices are commonly used for evaluating risks during the risk assessment process, there is little evidence to demonstrate that they improve decision-making, as they have a number of limitations, including potential inconsistencies and discrepancies when evaluating and ranking risks. These limitations suggest that physicians, physiotherapists and sports scientists should only use injury burden, risk matrices and risk contours when they fully understand their strengths and weaknesses.